PENGARUH DUKUNGAN SUAMI TERHADAP LAMA PERSALINAN KALA II PADA IBU PRIMIPARA - Diponegoro, A.M.; Budi Hastuti, S.F (Universitas Ahmad Dahlan, 2009)
The aim of research is to know whether the role of husband support toward the primipara mother during the first birth. The subjects were 78 primipara mothers. Forty primipara mothers were accompanied by their husbands and forty primipara mothers were not accompanied by their husbands. The research was conducted in health community centre in Yogyakarta district. The result showed the primipara mothers who were accompanied by their husbands were in better condition (p =0,004) compared to primipara mothers who were not accompanied by their husbands in second term condition.